Serenity and its relationship to prosocial and aggressive behaviors in Argentinean children - Cuello, Marina Ines (2014)
Serenity has been defined as a positive emotion that reflects feelings of inner peace and confidence. The development of serenity constitutes a valuable resource that enables children to cope with life stressors and to establish positive relationships with others. The present study examined serenity and possible gender group differences in Argentinean children. The second goal was to investigate the relation between serenity and prosocial and aggressive behaviors. Participants were 615 children aged 9 to 13 years (276 boys, 339 girls), from 11 public primary schools in the city of Buenos Aires, Argentina. Gender analyses showed no differences between boys and girls in serenity scores. As expected, serenity proved to be positively related to prosocial behaviors and negatively related to physical and verbal aggression. These results indicate that children who describe themselves as more serene are also prone to give help and comfort to others. Moreover, serene children appear to be less aggressive towards classmates. Evidence suggests that peer relations can be enhanced by the utilization of serenity skills in the school context.